Lower Plasma miR-223 Level Is Associated with Clopidogrel Resistance in Acute Coronary Syndrome: A Systematic Review and Meta-Analysis - Hang Cheng; Min Yang; Junli Hao; Kejie Chen; Quandan Tan; Song He; Fengkai Mao; Ming Yang; Yapeng Lin; Jie Yang (Journal of Interventional Cardiology)
Objectives. To evaluate the relationship between the plasma miR-223 expression level and clopidogrel resistance in acute coronary syndrome (ACS) patients. Methods. We performed a search for publications using online databases including PubMed, EMBASE, Cochrane Library, and Chinese Databases (CNKI database, Weipu database, and Wanfang database) from the inception of the databases to June 18, 2023, to identify studies reporting the relationship between the plasma miR-223 level and clopidogrel resistance in ACS patients. Two researchers independently searched and screened to ensure the consistency of the results and assess the quality of the included studies according to the Newcastle-Ottawa scale. A fixed-effects model was used for pooling data with STATA 14.0. Results. Four articles including 399 Chinese ACS patients were eligible for the meta-analysis. Low plasma miR-223 levels were independently correlated with clopidogrel resistance in Chinese ACS patients (OR 0.58, 95% CI: 0.33–1.04). Conclusion. Lower plasma miR-223 levels are associated with clopidogrel resistance in Chinese ACS patients, suggesting that miR-223 may be a potential diagnostic biomarker of clopidogrel resistance.